Preparation and Evaluation of Mechanical Properties of Aluminum Nanocomposite - Ramzan Muhammad, Mohammad Motamir (International Journal of Advanced Science and Technology, 2020)
Nanocomposite materials with metal matrix are commonly practiced by researchers for improving mechanical properties. In this study a novel nanocomposite was formulated by reinforcement of alumina-zirconia nanoparticles in pure aluminum. Sol-gel synthesis was used to obtain the nanoparticles and stir casting method was applied to formulate nanocomposite aluminum. The specimen was prepared for microstructural and mechanical characterization. It was found that the said nanocomposite performs excellently in hardness and wear resistance but poor in tension.